Granulomаtosis With Polyangiitis Affecting the Lung and Orbit - Zh. V. Sheikh; I. E. Tyurin; T. D. Safonova; A. M. Andreychenko (Вестник рентгенологии и радиологии, 2021)
The paper describes a clinical case of pulmonary and right orbital injuries in granulomatosis with polyangiitis in a 38-year-old male. The case is of considerable interest due to the rarity of this pathology, especially because of the localization in the orbital region. The information provided in this paper can help in the early and accurate diagnosis of granulomatosis with polyangiitis, which, in turn, will improve the prognosis of the disease.